Bacteriorhodopsin-based assemblies and their enhanced photoelectric and bioelectric properties - Li, Rui (2010)
Bacteriorhodopsin (bR) is one of the most attractive biomaterials used in bioelectronics. In this work, different bR-based biofilms are fabricated by incorporating functional materials to improve bR bioelectronic properties. A bR multilayered film is layer-by-layer constructed by using highly biocompatible poly-L-lysine as an efficient assembler to produce higher photocurrent than that of bR films built by other assemblers. An integrated bR/WO3•H2O/PVA membrane is developed to generate approximately six fold of photocurrent over bR alone, revealing an enhancement mechanism based on hydrogen spillover effect of WO3•H2O. Through nanocomposing bR and quantum dots (QDs), a novel bR-originated stationary photocurrent is obtained from a unique photocycle using QDs as nanoscale light sources. With the bidirectional mediation by dipoles in bR, the hole mobility of TiO2 nanowires FET is improved by a factor of 2. This work provides new approaches to significantly improve bioelectronic performance of bR while contribute in-depth fundamental knowledge in bioelectronics.